What Is the Nexus between Migration and Mobility? A Framework to Understand the Interplay between Different Ideal Types of Human Movement - Piccoli, Lorenzo; Matteo Gianni; Ruedin, Didier; Achermann, Christin; Dahinden, Janine; Paula Hoffmeyer-Zlotnik; Nedelcu, Mihaela; Zittoun, Tania (My University, 2024)
Categorising certain forms of human movement as ‘migration’ and others as ‘mobility’ has far-reaching consequences. We introduce the migration–mobility nexus as a framework for other researchers to interrogate the relationship between these two categories of human movement and explain how they shape different social representations. Our framework articulates four ideal-typical interplays between categories of migration and categories of mobility: continuum (fluid mobilities transform into more stable forms of migration and vice versa), enablement (migration requires mobility, and mobility can trigger migration), hierarchy (migration and mobility are political categories that legitimise hierarchies of movement) and opposition (migration and mobility are pitted against each other). These interplays reveal the normative underpinnings of different categories, which we argue are too often implicit and unacknowledged.
Keywords: borders; citizenship; migration; migration governance; migration policy; migration studies; mobility